2018
DOI: 10.1038/s41419-018-0881-6
|View full text |Cite
|
Sign up to set email alerts
|

TRIM52 plays an oncogenic role in ovarian cancer associated with NF-kB pathway

Abstract: Emerging evidence suggests that the members of the tripartite motif (TRIM) family play a crucial role in cancer development and progression. The purpose of the study was to explore TRIM52's role in tumorigenesis and its potential molecular mechanism in ovarian cancer. The study demonstrated that knockdown of TRIM52 in SKOV3 and CAOV3 cells inhibited ovarian cancer cell invasion, migration, and proliferation, and induced cell apoptosis. On the contrary, overexpression of TRIM52 in HO8910 cells showed contrary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 28 publications
4
63
0
Order By: Relevance
“…Tripartite motif (TRIM) proteins were the member of the RING family of E3 ubiquitin ligase, including RING-finger domain, Zinc-binding domain (B-boxes domain), Coiled-coil domain, and C-terminal domain, and the presence of RING finger indicated that TRIM protein as E3 participated in various physiological processes in cells [10][11][12][13]. Previous studies had reported the important functions of TRIM proteins in the development of various cancers, which played an important role in cell cycle, apoptosis, differentiation, metabolism, and immune response [14][15][16][17]. The clinical manifestations observed in human diseases caused by TRIM gene mutations might be due to change in TRIM activity during ubiquitination [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Tripartite motif (TRIM) proteins were the member of the RING family of E3 ubiquitin ligase, including RING-finger domain, Zinc-binding domain (B-boxes domain), Coiled-coil domain, and C-terminal domain, and the presence of RING finger indicated that TRIM protein as E3 participated in various physiological processes in cells [10][11][12][13]. Previous studies had reported the important functions of TRIM proteins in the development of various cancers, which played an important role in cell cycle, apoptosis, differentiation, metabolism, and immune response [14][15][16][17]. The clinical manifestations observed in human diseases caused by TRIM gene mutations might be due to change in TRIM activity during ubiquitination [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The tripartite motif23 may interact with these cytokines to positively regulate NF‐κB signaling. Recent studies have suggested that TRIM family proteins play a critical role in regulation of the NF‐κB pathway by ubiquitinating proteins at different steps . We performed GSEA analysis and found that high expression of TRIM23 was correlated with apoptosis resistance and DNA repair.…”
Section: Discussionmentioning
confidence: 93%
“…NF-kB (transcripton factor nuclear kappa B) is an important mediator that acts in the chronic inflammaton [37]. NF-kB was highly expressed in ovarian cancer and related to ovarian cancer progression [38,39] . Immunotherapies attenuate the levels of nuclear factor kappa B, reduce cell dynamics and effectively target the TLR-related downstream molecules, eliciting a protective effect against chemoresistance [40].…”
Section: Discussionmentioning
confidence: 99%